2000
DOI: 10.1016/s0165-5728(99)00226-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma levels of interleukin-1, interleukin-6 and α-1-antichymotrypsin in patients with Alzheimer's disease: peripheral inflammation or signals from the brain?

Abstract: Plasma concentrations of interleukin-1beta (IL-1beta), interleukin-6 (IL-6), C reactive protein (CRP) and alpha-1-antichymotrypsin (ACT) in 145 patients with probable Alzheimer's disease (AD) and 51 non-demented controls were measured. To investigate the cellular activation of peripheral immune system, plasma levels of neopterin were also investigated. Plasma levels of IL-1 were detectable in 17 patients with AD (13%) and only in one control (2%) and average levels of IL-1 were higher in AD patients than in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
221
1
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(245 citation statements)
references
References 42 publications
14
221
1
4
Order By: Relevance
“…First, our cross-sectional study design precludes causal interpretations. Indeed, there is much debate about whether peripheral cytokine levels are the cause or consequence of brain inflammation (62) and it is possible that raised circulating IL-6 reflects spillover from the central nervous system and is thus a marker of subclinical neuroinflammatory conditions (63). It is also possible that the relationship between peripheral IL-6 levels and hippocampal grey matter volume are independently accounted for by a third, possibly genetic, factor.…”
Section: Discussionmentioning
confidence: 99%
“…First, our cross-sectional study design precludes causal interpretations. Indeed, there is much debate about whether peripheral cytokine levels are the cause or consequence of brain inflammation (62) and it is possible that raised circulating IL-6 reflects spillover from the central nervous system and is thus a marker of subclinical neuroinflammatory conditions (63). It is also possible that the relationship between peripheral IL-6 levels and hippocampal grey matter volume are independently accounted for by a third, possibly genetic, factor.…”
Section: Discussionmentioning
confidence: 99%
“…14 Data supporting the idea that peripheral IL-6 levels represent those in brain is lacking, but evidence suggests that IL-6 does cross the blood brain barrier and peripheral levels may represent spillover from the central nervous system and be a marker of inflammation. 15,16 Interleukin 6 may also affect cognition through an interaction with vascular disease as there is evidence that it increases the risk of diabetes mellitus and cardiovascular events. 17, 18 In addition, the finding that IL-6 and CRP levels above the median have predicted cognitive decline in those with, but not without, the metabolic syndrome implicates a vascular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that inflammatory markers, such as interleukin-6 (IL-6), interleukin-12 (IL-12), tumor necrosis factor-a (TNFa), and C-reactive protein (CRP), are elevated in the elderly and are associated with cognitive impairment and decline (Licastro et al, 2000;Engelhart et al, 2004;Dimopoulos et al, 2006;Alvarez et al, 2007;Zuliani et al, 2008;Trollor et al, 2011), as well as increased risk of mortality .…”
Section: Introductionmentioning
confidence: 99%